DIAGRAM VEE SEBAGAI MEDIA DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN BIOLOGI - suryaningsih, yeni (Papanda Journal of Mathematics and Science Research, 2022)
In facing the challenges of the globalization era, it is necessary to have the role of human resources who have the ability to think critically to solve problems with abstract thought processes and arrange them in an effective way of solving. Biology learning as part of science learning has an important role in improving the quality of education and producing quality students, namely humans who are able to think critically, creatively and logically. In developing critical thinking skills, students need to master biological concepts and be trained to find solutions related to phenomena that occur. This cannot be done by applying conventional methods, but there is a need for learning media that support students to explore and find concepts so that students are actively involved in learning. Learning by using Vee Diagram media as an effort to develop students' critical thinking skills so as to make student learning more meaningful and familiarize students in combining a theory with methodology as well as getting conclusions and values ​​that provide benefits from what they learn